2013
DOI: 10.1073/pnas.1321748111
|View full text |Cite
|
Sign up to set email alerts
|

Early hypercytokinemia is associated with interferon-induced transmembrane protein-3 dysfunction and predictive of fatal H7N9 infection

Abstract: Significance A unique avian-origin H7N9 influenza virus caused 134 human infections with 44 deaths. The host factors contributing to moderate vs. severe disease are not clear. Here, we show that H7N9 severity was associated with a higher level of cytokines/chemokines. We demonstrate that the cytokines in the infected lung were 100- to 1,000-fold higher than those in the plasma. Furthermore, we found that the IFN-induced transmembrane protein-3 (IFITM3) C/C genotype was associated with severe clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
311
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(332 citation statements)
references
References 21 publications
20
311
0
Order By: Relevance
“…Earlier studies showed that IP-10, IL-6, IL-8, IL-10, MCP-1, MIG and MIP-1b were dramatically increased in severe H7N9 cases and H5N1 cases compared to controls (Peiris et al, 2004;de Jong et al, 2006;Chi et al, 2013;Zhou et al, 2013;Shen et al, 2014;Wang et al, 2014b;Wu et al, 2014). However, these cytokines in mild/asymptomatic H7N9 cases were similar to those in controls except that the level of IP-10 increased very slightly.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Earlier studies showed that IP-10, IL-6, IL-8, IL-10, MCP-1, MIG and MIP-1b were dramatically increased in severe H7N9 cases and H5N1 cases compared to controls (Peiris et al, 2004;de Jong et al, 2006;Chi et al, 2013;Zhou et al, 2013;Shen et al, 2014;Wang et al, 2014b;Wu et al, 2014). However, these cytokines in mild/asymptomatic H7N9 cases were similar to those in controls except that the level of IP-10 increased very slightly.…”
mentioning
confidence: 79%
“…Previous studies with highly pathogenic avian influenza A (H5N1) virus as well as pandemic (H1N1) 2009 virus suggested that poor prognosis in humans with these viruses might be attributed to a cytokine storm or hypercytokinaemia in the host (Peiris et al, 2004;de Jong et al, 2006;To et al, 2010). Some studies with H7N9 virus also showed the presence of high levels of a series of cytokines and chemokines, such as IP-10, IL-6, IL-8, IL-10, MCP-1, MIG and MIP-1b, in human infections with severe disease with or without fatal outcomes (Chi et al, 2013;Zhou et al, 2013;Shen et al, 2014;Wang et al, 2014b;Wu et al, 2014). It should be noted that investigation on the profiles of cytokines and chemokines induced in mild/asymptomatic cases will aid in assessing their role in mild/asymptomatic versus severe/fatal outcomes of infection with H7N9 and the role of innate immunity and provides a new perspective on the evaluation of prognosis and the innovation of treatment.…”
mentioning
confidence: 99%
“…The cytokine storm caused by cytokine dysregulation after infection is an important cause of serious symptoms and of high mortality. Recent studies have shown that several cytokines are present at higher-than-normal levels in serum samples obtained from H7N9 patients (Chi et al, 2013;Wang et al, 2014;Zhou et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Most H7N9 patients have a high fever and cough at the onset of the illness, and rapidly develop lower respiratory tract infections, which cause severe symptoms (Gao et al, 2013a;Shen et al, 2014). H7N9 infection causes pneumonia and acute respiratory distress syndrome (ARDS), which result in a case fatality rate of more than 30 % (Chi et al, 2013;Wang et al, 2014;Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation